(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Today, internet is the storage of huge information. Therefore it is very serious issue to get data fast and efficiently. Text summarization plays an important role in the field of information retrieval. Text summarization is a process of representing a text in concise way with same sense. This hybrid approach mainly based on extractive summarization. The proposed approach combines the concept of statistical measure, sentiment analysis and finally uses the concept of fuzzy logic to select sentence. Based on the level of importance of the sentence, summary is created.